Odnos između HBV RNK nivoa i ishoda trudnoće među nosiocima hepatitisa B: HBV RNA Level & Pregnancy Outcomes in Hepatitis B Carriers - Zhang, Manman; Liao, Xin; Wang, Heng; Wu, Huan; Zhang, Baofang (Journal of Medical Biochemistry, 2024)
Background: This study aims at investigating the relationship HBV RNA level and pregnancy outcomes among hepatitis B carriers.Methods: A total of 562 pregnant women who attended the Affiliated Hospital of Guizhou Medical University (Guizhou, China) from June 2020 to June 2023 were collected, 203 HBV carriers was included in this study. Then we recorded general data and pregnancy outcomes, the levels of HBV DNA, HBV RNA and HBeAg status in HBV carrier were detected. Pregnancy outcomes including intrahepatic cholestasis of pregnancy (ICP), gestational hypertension (GH), pre-eclampsia, gestational diabetes mellitus (GDM), preterm prelabour rupture of membranes (PPROM), mode of delivery , preterm birth, low birth weight (LBW) and macrosomia. Results: 562 pregnancies were analyzed, 203(36.12%) were infected with hepatitis B virus. Compared with HBsAg negative, HBsAg positive pregnant women had a higher risk of ICP. No statistically significant differences were found in the rates of GDM, GH, pre-eclampsia, PPROM, preterm birth, LBW, macrosomia and mode of delivery among women with the two groups. The analysis of risk factors of ICP showed that maternal HBV RNA level (OR = 3.814, 95% CI: 2.036~7.142, P< 0.001) was an important risk factor for ICP in HBsAg positive pregnant women. The receiver operating characteristics (ROC) curve revealed that the areas under the HBV RNA was 0.8652(95% confidence interval 0.7636~0.9669, P< 0.001).Conclusion: HBV RNA level pose significant negative impact to the pregnancy outcomes. It can be used as indicators to guide the prevention of ICP and improve maternal outcomes.